Overcoming climate and conflict: Promoting peace and resilience in a post-conflict region of the Philippines - Gadeberg, Marianne; Mascarenhas, Martina (2024)
In the post-conflict Mindanao region, Philippine authorities are working to reintegrate those communities living in former rebel strongholds into society. The in collaboration with Mindanao State University has conducted research, launched a community of practice, and put forward recommendations to ensure that new livelihood programs foster peace and climate resilience.